Minority policies in the Muslim world - Md. , Moniruzzaman (Bangladesh Institute of Islamic Thought (BIIT), 2014)
The Muslim world hosts a wide diversity of minority groups in terms of ethnicity, religion, language and culture. The minority diversity in some countries is overwhelming compared to others. Such diversities have put the countries in difficult position for national unification in the nation-building process. This article examines the minority policies of the Muslim countries in the context of majority syndrome. The minority policy is looked at from the perspective of government attitude towards four major international conventions in terms of ratification and accession. It argues that higher the ratification rate, fairer the minority policy of a country. The study found that the Muslim countries have mostly either ratified or accessed to three out of four conventions. In terms of inter-regional trend, the African, South and Southeast Asian and Central Asian countries are mostly comfortable with all the conventions. The Arab countries, however, show most irregular pattern.